Peak Aerobic Capacity in Adults With Cystic Fibrosis Stratified by Lung Disease Severity: A Retrospective Chart Review. Issue 3 (September 2015) - Swisher, Anne K.; Pepe, Anna; Weckesser, Jaime; Orenstein, David; Hebestreit, Helge
Abstract : Purpose: Exercise capacity in people with cystic fibrosis (CF) is an important factor in length and quality of life. Currently, there is no standard for testing, particularly for the growing population of adults with CF. This study was designed to describe maximal aerobic capacity in adults with varying degrees of CF lung disease severity as compared with similarly aged healthy controls using the Godfrey exercise test protocol. Methods: Results of maximal exercise tests were collected from 3 CF centers (total of 56 CF tests, mean age, 25 years) and compared with results of tests performed on healthy controls (n = 141, mean age 24 years). Cystic fibrosis tests were analyzed by lung disease severity (none, mild, moderate, and severe), and analyses of variance were performed to determine the relationships between lung disease severity and exercise variables. Results: Subjects with mild (forced expiratory volume in 1 second > 70% predicted) CF lung disease did not differ from healthy controls for peak exercise capacity (VO2 peak 2.47 L/min CF vs. 2.67 L/min control); however, as lung disease progressed to moderate or severe disease, exercise performance was significantly worse than controls. Conclusions: Adults with mild CF lung disease had exercise capacity that did not differ from the control group, but as the disease severity progresses, lower exercise capacity can be expected. This suggests that patients with mild lung disease should be encouraged to participate in regular exercise to maintain this function as lung disease progresses. Exercise prescription may need to be adapted for those with moderate or severe lung disease to account for declines in maximal exercise capacity.